Unsafe motherhood : Mayan maternal mortality and subjectivity in post-war Guatemala - Berry, Nicole S., 1970- (Fertility, reproduction, and sexuality ;, 2010)
Since 1987, when the global community first recognized the high frequency of women in developing countries dying from pregnancy-related causes, little progress has been made to combat this problem. This study follows the global policies that have been implemented in Sololá, Guatemala in order to decrease high rates of maternal mortality among Indigenous Mayan women. The author examines the diverse meanings and understandings of motherhood, pregnancy, birth and birth-related death among the biomedical personnel, village women, their families, and midwives. These incongruous perspectives, in con.